What matters to patients? A systematic review of preferences for medication-associated outcomes in mental disorders. Issue 4 (8th April 2015) - Eiring, Øystein; Landmark, Brynjar Fowels; Aas, Endre; Salkeld, Glenn; Nylenna, Magne; Nytrøen, Kari
Abstract : Objective: To investigate patients' preferences for outcomes associated with psychoactive medications. Setting/design: Systematic review of stated preference studies. No settings restrictions were applied. Participants/eligibility criteria: We included studies containing quantitative data regarding the relative value adults with mental disorders place on treatment outcomes. Studies with high risk of bias were excluded. Primary and secondary outcome measures: We restricted the scope of our review to preferences for outcomes, including the consequences from, attributes of, and health states associated with particular medications or medication classes, and process outcomes. Results: After reviewing 11 215 citations, 16 studies were included in the systematic review. These studies reported the stated preferences from patients with schizophrenia (n=9), depression (n=4), bipolar disorder (n=2) and attention deficit hyperactive disorder (n=1). The median sample size was 81. Side effects and symptom outcomes outnumbered functioning and process outcomes. Severe disease and hospitalisation were reported to be least desirable. Patients with schizophrenia tended to value disease states as higher and side effects as lower, compared to other stakeholder groups. In depression, the ability to cope with activities was found to be more important than a depressed mood, per se. Patient preferences could not consistently be predicted from demographic or disease variables. Only a limited number of potentially important outcomes had been investigated. Benefits to patients were not part of the purpose in 9 of the 16 studies, and in 10 studies patients were not involved when the outcomes to present were selected. Conclusions: Insufficient evidence exists on the relative value patients with mental disorders place on medication-associated outcomes. To increase patient-centredness in decisions involving psychoactive drugs, further research—with outcomes elicited from patients, and for a larger number of conditions—should be undertaken. Trial registration number: PROSPERO CRD42013005685.